Metastatic Tissue Detection in Lymphnodes Using Convolutional Neural Networks - Dr. K. Ramaabirami, Swathy R, Sornambikai R (International Journal of Advanced Science and Technology, 2020)
Healthcare industry is completely different from other industries where high priority and highest levels of care is expected in the services provided regardless of cost. Even though it consumes a huge percentage of budget it did not meet th eexpectations. Medical experts in their respective fields of expertise view the collected medical data. Due to its subjectivity, nature of the image, vast variations between different interpreters and exhaustion, it is very limited in terms of image interpretation by human expert. After being successful in other real world applications, deep learning is also providing creative solutions with good accuracy forimage analysis and is believed to provide innovative solutions for future applications in health care industry. In this chapter, we discussed the usage of convolution neural networks and its optimization used for metastatic tissue identification in histopathological scans of lymphnodes.